La comprensión lectora y el rendimiento académico en los estudiantes de la Escuela de Educación Básica “Península Ibérica” del barrio Centro Cívico, parroquia El Lucero, periodo 2023 - 2024. - Gaona Gaona, Rosa Angélica (2023)
The current research project supports the importance of stimulating reading comprehension, taking it as the fundamental basis for the development of learning and therefore improving the academic performance of students. The objective of the research is to analyze the reading comprehension and academic performance of the students of the "Península Ibérica" High School of the Centro Cívico Neighborhood, El Lucero Parish, period 2023 - 2024, it had a mixed-type approach framed in a non-experimental design, its scope is descriptive, the methods used were: Inductive-deductive, analytical-synthetic and the sample corresponds to 17 students of the elementary and middle sub-level to whom the diagnostic test and the PROLEC-R test were applied, obtaining results of low academic performance in the first levels of education, difficulties in the recognition of letters, sentence formation and articulation of words, In addition, according to the results, an alternative proposal called " Aprendemos leyendo " was designed, which is structured with different innovative activities to improve the reading comprehension of the students, which in turn has digital tools that help to complement the learning and improve the tutorial action. Keywords: Innovative activities, reading comprehension, digital tools, academic performance,